The library of the genius: The manuscript collection of Rasmus Christian Rask - Silvia Hufnagel (Tabularia)
The Arnamagnæan Institute at the University of Copenhagen houses the Old Norse-Icelandic manuscript collection of the famous Danish linguist Rasmus Rask (1787-1832) that comprises 127 post-medieval volumes. The topics covered in the manuscripts reflect Rask’s widespread interests and range from literature to non-fictional works, such as linguistics, history, law and liturgy. It seems that Rask’s large network of friends and acquaintances was of help in his efforts of acquiring manuscripts. Three of them are discussed in greater detail in this article: Rask 16 (nineteenth century) contains the lexicon of Jón Ólafsson from Svefneyjar with Rask’s notes, Rask 32 (eighteenth century) containing Old Norse-Icelandic romances, and Rask 98 (seventeenth century) containing 223 Icelandic songs with musical notations.